Under pressure. - De Cunto, Angela; Berti, Irene; Minute, Marta; Longo, Giorgio (Eur J Pediatr, 2013)
Physical urticaria is a rare but challenging subset of chronic urticaria. Wheals of pressure urticaria are typically delayed in appearance. A pressure test can easily be done to confirm the diagnosis.
Keywords: Child; Humans; Male; Pressure; Urticaria